Overcoming Obstacles to Successful Culture Change - Kotter, John; Kotter, John; Akhtar, Vanessa; Gupta, Gaurav (MIT Sloan Management Review, 2021)
Typical approaches to culture change -- relying on leaders to define the culture and cascade it throughout the organization, or fully outsourcing the responsibility of shaping and building culture to an HR group -- rarely produce real results. Instead, when individuals' behavior and actions become habits, it can truly change a culture. The authors explore three of the most widespread dangers to culture change and provide proven strategies for addressing them.